Perancangan Dan Penerapan Sistem Pencatatan Akuntansi Pada Toko Andi Com Jaya - Robby Krisyadi; Novilim Novilim (Universitas Internasional Batam, 2021)
The accounting recording system plays an important role in providing accounting information for a business partner. A general problem that exists in Andi Com Jaya store is lack of an effective and efficient accounting recording system, so that the provision of financial information cannot be maximally known. This program began by directly reviewing the activities of business operations and understanding the business procedure in Andi Com Jaya store. The next phase is creating an accounting system using Microsoft Office Access that suits with the store condition. The accounting system includes transactions for economic activities, operational activities, as well as the accurate financial reports. The completed system then was implemented to Andi Com Jaya store. The accounting recording system which has done designed was successfully implemented to Andi Com Jaya store. Manifested financial information can provide an overview for the owner regarding the store’s financial condition and decision making for future developments in the business ventures.